2021
DOI: 10.5664/jcsm.8856
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of interactive associations of sleep and pain with cognition in sedentary middle-aged and older adults

Abstract: Study Objectives: The objective of this study was to examine independent and interactive associations between self-reported sleep (sleep efficiency and total sleep time [TST]) and pain with cognition in sedentary middle-aged and older adults. Methods: Seventy-five sedentary adults at least 50 years of age (M age = 63.24, standard deviation = 8.87) completed 14 daily diaries measuring sleep and pain. Weekly average sleep efficiency, TST, and pain were computed. Participants also completed computerized cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Furthermore, excessive sleep duration can impair cognitive and physiological function in older adults (50). Curtis et al found that the association between self-reported sleep and cognitive performance interacted with pain in sedentary adults aged 50 years and above (51). Older adults have less energy, spend less time being physically active, and often maintain a sedentary lifestyle, which can lead to a decline in physical health (52).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, excessive sleep duration can impair cognitive and physiological function in older adults (50). Curtis et al found that the association between self-reported sleep and cognitive performance interacted with pain in sedentary adults aged 50 years and above (51). Older adults have less energy, spend less time being physically active, and often maintain a sedentary lifestyle, which can lead to a decline in physical health (52).…”
Section: Discussionmentioning
confidence: 99%